Avaliação in vitro das microdeformações em implantes curtos, com conexão protética cone morse e diferentes desenhos de roscas, convencionais e platôs - Sousa, Talitha de Cássia Silva [UNESP] (2014)
The aim of this in vitro study was to evaluate by means of strain gauge analysis, the stress distribution around and in two vertical levels of short morse taper threaded implants with morse taper threaded implants with conventional screws and Bicon plateaus implants through gauge test. In each polyurethane block (n=10), two implants with each type of design were installed. For the conventional screws implant, the solid abutment was screwed with a torque of 20 N.cm and for the plateau implant,the abument was seated right inside the implant with the aid of a hammer. Four strain gauges were glued tangent to each implant, positioned diametrically opposed. Two strain gauges were also adhered to the middle third and the other one in the apical third. Axial static loads of 30 kg were performed on the abutments during 10 seconds,with the aid of a load device (DAC). The data obtained in the gauge test werw submitted to statistical analysis using ANOVA and Sidak´s tests (5%).The results showed that the implants(p=0.00029 < 0.05), the region(horizontal and vertical) (p= 0.0001 <0.05), as well as the interaction effect(p=0.02044<0.05) were statistically significant. It follows that themicro-strains are greatest for the implant with plateaus and horizontal micro-strain are larger compared to both the vertical implants